Analysis of the Relationship between Health Protocols and the Event of Coronavirus Disease 2019 (COVID-19) in Mandailing Natal Regency in 2021 - Rahmadani Rahmadani; Fazidah Aguslina Siregar; R. Kintoko Rochadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to determine and analyze the relationship between health protocols and the event of coronavirus disease 2019 (COVID-19) in Mandailing Natal Regency in 2021. This type of research was a quantitative analytic survey with a case-control design. The population in this study were residents of Mandailing Natal Regency aged 16-55 years who were new cases or old cases who had participated in the swab polymerase chain reaction (PCR) test with positive or negative results with the final result of recovering alive recorded under the supervision of the COVID-19 Task Force (July-November 2021). Based on the sample calculation, the minimum sample size obtained is 27 people for the case sample and 27 people for the control. So the minimum total sample is 54 respondents with a ratio of one to one (1:1). Data processing is carried out with the stages of editing, coding, entry, and cleaning before data analysis is carried out, then checks and repairs are carried out. Data analysis used bivariate analysis. The results showed that the health protocols category for the use of mask obtained p-value=0.036, meaning that there has relationship between the use of mask and the incidence of COVID-19. Washing hand with soap has no relationship with the incidence of COVID-19 with p-value=0.781. Maintaining a minimum distance of 1 meter has no relationship with the incidence of COVID-19 with a p-value=0.739. Limiting activities outside the home has relationship with the incidence of COVID-19 with a p-value=0.034. The category away from the crowd has relationship with the incidence of COVID-19 with a p-value=0.002.